2020
DOI: 10.3390/brainsci10030165
|View full text |Cite
|
Sign up to set email alerts
|

Pre-School Teachers’ Knowledge, Belief, Identification Skills, and Self-Efficacy in Identifying Autism Spectrum Disorder (ASD): A Conceptual Framework to Identify Children with ASD

Abstract: Recently, the identification and detection of children with autism spectrum disorder (ASD) has become an essential issue under ASD intervention services. The high percentage of ASD among children requires preschool teachers to recognizse children’s abnormal development and identify them at an early stage, followed by referral to specialists. Therefore, this identification calls for a specific ability among preschool teachers, identified as knowledge, belief, identification skills, and self-efficacy (KBISSE). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 87 publications
1
14
0
1
Order By: Relevance
“…Overall, in this review we found a lack of knowledge in most of the articles reviewed coinciding with prior reviews [61,62] and other studies [45]. We found that most of the articles revealed low [64,66,68,71,75,76,79,[84][85][86]95] or medium [65,67,73,74,77,78,80,82,91] levels of knowledge about ASD among their participants, coinciding with prior studies [21,25,36,37].…”
Section: Teachers' Knowledge Of Asd and Moderators That Possibly Influence Asdsupporting
confidence: 76%
See 2 more Smart Citations
“…Overall, in this review we found a lack of knowledge in most of the articles reviewed coinciding with prior reviews [61,62] and other studies [45]. We found that most of the articles revealed low [64,66,68,71,75,76,79,[84][85][86]95] or medium [65,67,73,74,77,78,80,82,91] levels of knowledge about ASD among their participants, coinciding with prior studies [21,25,36,37].…”
Section: Teachers' Knowledge Of Asd and Moderators That Possibly Influence Asdsupporting
confidence: 76%
“…Early research literature has already collected articles examining teachers' knowledge regarding ASD. A review carried out in 2020 [61] built a conceptual framework of teachers' knowledge through 11 studies. The authors concluded that early childhood teachers have a lack of knowledge identifying students with ASD.…”
Section: Early Literature About Teachers' Knowledge Regarding Asdmentioning
confidence: 99%
See 1 more Smart Citation
“…Autism or autism spectrum disorder (ASD) is a condition that impacts a child’s development in two core areas: the first is social communication and social interaction, and the second is restricted, repetitive patterns of behavior and interests [ 1 ]. As the number of children with ASD is increasing globally, concerns about their neurocognitive and behavioral problems are rising [ 2 , 3 ]. Statistics indicated that at least one in 600 children in Malaysia has ASD [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…(5) Treatment and intervention; (6) Etiopathogenesis (Biomarkers, Biology, Genetic, Epigenetic and Risk Factor); (7) Autism and comorbidity; (8) Autism and adulthood; and (9) Broader Autism Phenotype (BAP).…”
Section: Introductionmentioning
confidence: 99%